Effects of norms, warm-glow and time use on household recycling - Bente Halvorsen (Statistics Norway, Research Department, 2004)
The aim of this paper is to quantify the relative importance of motivations based on warm-glow, social and moral norms and cost of time used recycling on household recycling efforts. We also test for crowding-out of intrinsic motivations when recycling is perceived as mandatory. We find that the most important variable increasing household recycling efforts is agreeing that recycling is a pleasant activity in itself, which may be interpreted as a warm-glow effect. The most important variable reducing household recycling is the opportunity cost of time spent recycling. We find no evidence of crowding-out of intrinsic motivation when recycling is perceived as mandatory. On the contrary, we find that governmental legislation increases household recycling efforts on most materials.
Keywords: C20; C35; D12; D60; H42; H79; Q29; 330; Contingent valuation method; cost of time; household recycling; moral and social norms; ordered probit; simultaneous estimation of discrete- and continuous choice; warm-glow; crowding out.